(untitled) (Quinto Sol, 2023)
The article deals with the juicio de residencia carried out against the federal Governor of Jujuy (Argentina) Pablo Alemán. Both the judicial and political process as well as the conditions of possibility that explain the trial at a time of decisive political redefinitions in the north of the Argentine Confederation are studied in depth. We are interested in knowing who intervened in the judicial process, how it was carried out, what arguments the accusations supported and which political representations could be read in the situation, as well as the meaning that the trial had in the framework of provincial power.